The EuroHeart Failure survey programme-- a survey on the quality of care among patients with heart failure in Europe. Part 1: patient characteristics and diagnosis. - Cleland, J; Swedberg, K; Follath, F; Komajda, M; Cohen-Solal, A; Aguilar, J; Dietz, R; Gavazzi, A; Hobbs, R; Korewicki, J; Madeira, H; Moiseyev, V; et al. (2003)
BACKGROUND: The European Society of Cardiology (ESC) has published guidelines for the investigation of patients with suspected heart failure and, if the diagnosis is proven, their subsequent management. Hospitalisation provides a key point of care at which time diagnosis and treatment may be refined to improve outcome for a group of patients with a high morbidity and mortality. However, little international data exists to describe the features and management of such patients. Accordingly, the EuroHeart Failure survey was conducted to ascertain if appropriate tests were being performed with which to confirm or refute a diagnosis of heart failure and how this influenced subsequent management. METHODS: The survey screened consecutive deaths and discharges during 2000-2001 predominantly from medical wards over a 6-week period in 115 hospitals from 24 countries belonging to the ESC, to identify patients with known or suspected heart failure. RESULTS: A total of 46788 deaths and discharges were screened from which 11327 (24%) patients were enrolled with suspected or confirmed heart failure. Forty-seven percent of those enrolled were women. Fifty-one percent of women and 30% of men were aged >75 years. Eighty-three percent of patients had a diagnosis of heart failure made on or prior to the index admission. Heart failure was the principal reason for admission in 40%. The great majority of patients (>90%) had had an ECG, chest X-ray, haemoglobin and electrolytes measured as recommended in ESC guidelines, but only 66% had ever had an echocardiogram. Left ventricular ejection fraction had been measured in 57% of men and 41% of women, usually by echocardiography (84%) and was <40% in 51% of men but only in 28% of women. Forty-five percent of women and 22% of men were reported to have normal left ventricular systolic function by qualitative echocardiographic assessment. A substantial proportion of patients had alternative explanations for heart failure other than left ventricular systolic or diastolic dysfunction, including valve disease. Within 12 weeks of discharge, 24% of patients had been readmitted. A total of 1408 of 10434 (13.5%) patients died between admission and 12 weeks follow-up. CONCLUSIONS: Known or suspected heart failure comprises a large proportion of admissions to medical wards and such patients are at high risk of early readmission and death. Many of the basic investigations recommended by the ESC were usually carried out, although it is not clear whether this was by design or part of a general routine for all patients being admitted regardless of diagnosis. The investigation most specific for patients with suspected heart failure (echocardiography) was performed less frequently, suggesting that the diagnosis of heart failure is still relatively neglected. Most men but a minority of women who underwent investigation of cardiac function had evidence of moderate or severe left ventricular dysfunction, the main target of current advances in the treatment of heart failure. Considerable diagnostic uncertainty remains for many patients with suspected heart failure, even after echocardiography, which must be resolved in order to target existing and new therapies and services effectively.